The grammar and poetics of Mūrti-Sevā - Valpey, K (2004)
This thesis offers a multi-faceted exploration of image worship theology and practice within a Vaishnava Hindu theistic devotional tradition founded in the sixteenth century, flourishing today largely in north and northeast India and, since recently, spreading worldwide. The thesis serves two aims. First, it augments existing scholarship on Hindu temple image worship and Caitanya (Gaudīya) Vaishņavism by focusing on two contemporary temple communities one in the north Indian pilgrimage centre Vrindavan, the second near Watford, outside London. These represent, respectively, an "embodied community" and a "missionizing tradition," following Barbara Holdrege's typology in her studies of Hindu and Jewish traditions. By considering the practice of worship (mūrti-sevā) in terms of two persistent themes, namely rule-governed practice (vaidhī-sādhana) and emotion-driven practice (rāgānuga-sādhana), I show how the elements of "embodiment" and "missionizing" blend to produce variations on the overarching theme of Krsna bhakti, devotion to Kŗşna as the supreme divinity. Second, by focusing on the divine image in these two temples and the practice of worship, I offer one study of how "religious truth" is understood within these communities in terms of three dimensions of truth proposed by the Comparative Religious Ideas Project at Boston University (1995-1999; Robert C. Neville, et al., Religious Truth, State University of New York Press, 2001). At the same time I offer an attempt to extend the scope of that project by adding the dimensions of physical image and ritual practice to its existing dimension, religious ideas. I show how the central notion of devotion to Kŗşna as God (bhagavān) entails a complex web of discursive, ritual, and narrative expression to sustain image worship as a truth of embodiment/practice (the opposite of failure) which is also expressive truth (the opposite of deceit) that follows from propositional/epistemological truth (the opposite of error).